KARANG TARUNA SEBAGAI AGEN PEMBERDAYAAN PEMUDA: TELAAH TERHADAP MEDIA SOSIAL - Fadhiela, Adhienda; Lessy, Zulkipli (Universitas Cokroaminoto Yogyakarta, 2023)
Social capital is required as an initial asset for empowerment in social walfare efforts. Just like in the case of Bawuran Village, there is potential among the youth that needs to be empowered through the youth organization, known as karang taruna. Therefore, the need for social capital as a tool assess the extent of the empowerment in carrying out its functions and duties is crucial. This research aims to determine the analysis of social capital in the empowerment of the Bawuran karang taruna organization. The methodology used in this research is qualitative with a descriptive analysis research type. The data collection methods employed include observation, interviews, and documentation. Subsequently, the data analysis method used is based on Miles and Huberman, consisting of data reduction, data presentation, and drawing conclusions. The results of this research indicate that in the trust component of the karang taruna organization, there is still a lack of trust. In the norm component of the empowerment of the karang taruna organization, deviations from individual youth will result in reprimands. Social networks collaborate well from within the village, such as the village government, disaster preparedness village, and youth in the hamlet. Meanwhile, from outside the village, it consists of the Social Affairs Agency, Agriculture Agency, Cultural Agency, BNN, and Djarum76.